2008
DOI: 10.1007/s12237-008-9077-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Replete Benthic Microalgae as a Source of Dissolved Organic Carbon to Coastal Waters

Abstract: Dissolved organic carbon (DOC) flux dynamics were examined in the context of other biogeochemical cycles in intertidal sediments inhabited by benthic microalgae. In August 2003, gross oxygenic photosynthetic (GOP) rates, oxygen penetration depths, and benthic flux rates were quantified at seven sites along the Duplin River, GA, USA. Sediments contained abundant benthic microalgal (BMA) biomass with a maximum chlorophyll a concentration of 201 mg chl a m −2 . Oxygen microelectrodes were used to determine GOP ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 73 publications
2
22
1
Order By: Relevance
“…MPB are a potential source of water-column DOC (Porubsky et al 2008). However, DOC derived from MPB represented only a small fraction of the total DOC efflux from sediments in the current study (0.4% during the first dark incubation, when excess 13 C flux as DOC was highest) and was a minor pathway for loss of 13 C fixed by MPB (2.64% over 33 d).…”
Section: Discussioncontrasting
confidence: 57%
“…MPB are a potential source of water-column DOC (Porubsky et al 2008). However, DOC derived from MPB represented only a small fraction of the total DOC efflux from sediments in the current study (0.4% during the first dark incubation, when excess 13 C flux as DOC was highest) and was a minor pathway for loss of 13 C fixed by MPB (2.64% over 33 d).…”
Section: Discussioncontrasting
confidence: 57%
“…Until now, the influence of chemical factors on DNRA and denitrification in sediments has been assessed by slurry incubations (4,12,30), by flux measurements with sealed sediment cores (7, 47) or flowthrough sediment cores (16,27,37), and in one case, in reconstituted sediment cores sliced at centimeter-level resolution (39). Here, we present a new method, the combined gel probe and isotope labeling technique, to determine the vertical distribution of the net rates of DNRA in sediments.…”
Section: Dissimilatory Nomentioning
confidence: 99%
“…Conventional methods to investigate the relative importance of different pathways of dissimilatory NO 3 Ϫ reduction in sediments include slurry incubations (4,12,30), methods that use sealed sediment cores (7,47), and methods that use flowthrough sediment cores (16,27,37). Only one study used reconstituted sediment cores in which DNRA activity was measured at centimeter-level resolution (39).…”
Section: Nhmentioning
confidence: 99%
“…Diverse assemblages of benthic algae and microalgae have been reported to live at the sediment-water interface, and those assemblages can greatly alter the mass transfer of remineralized nutrients from the buried sediments to the overlying water column (McGlathery, Sundbäck, and Anderson, 2004;Porubsky, Veasquez, and Joye, 2008;Seitzinger and Pilling, 1992;Sundbäck et al, 1991;Sundbäck and Granéli, 1988;Yarbro and Carlson, 2008). Studies have reported that the biomass associated with a thin layer of benthic algae can account for nearly one-third of the primary production in estuarine systems and that benthic algae can be distributed widely across open-sand bottom habitats (Cahoon and Cooke, 1992;Pinckney and Zingmark, 1993).…”
Section: Pore-water Nutrient Flux and Exchangementioning
confidence: 99%